Small Holdings and Agricultural Co-operation in England - Fay, C. R. (Quarterly Journal of Economics, 1910)
The influence of America on English Agriculture, 499. — The Small Holdings Act of 1908, 501. — The application in the County of Cambridgeshire, 502. — Difficulties and achievements, 503. — The experiment at the Tile House Farm, Soham, 504. — Partial adoption of co-operation, 505. — Varying success of agricultural co-operation in England and on the Continent of Europe, 506. — Problems of co-operative sale, 509. — Conclusions, 513.